The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1414-431x20165176
|View full text |Cite
|
Sign up to set email alerts
|

Multiple facets of HIV-associated renal disease

Abstract: HIV infection has a broad spectrum of renal manifestations. This study examined the clinical and histological manifestations of HIV-associated renal disease, and predictors of renal outcomes. Sixty-one (64% male, mean age 45 years) HIV patients were retrospectively evaluated. Clinical presentation and renal histopathology were assessed, as well as CD4 T-cell count and viral load. The predictive value of histological lesion, baseline CD4 cell count and viral load for end-stage renal disease (ESRD) or death were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Although the two risk alleles were significantly connected to higher odds of HIVAN, APOL1 genotype did not predict confidently this specific histopathology and cannot eliminate the important role of kidney biopsy in the clinical care of HIV-positive blacks who are with proteinuria more than 3.5 mg/24 h urine or unexplained kidney disease [ 38 ]. The findings of Da Silva et al in 2016 also strengthen the importance of renal biopsy in HIV patients with kidney impairment and/or proteinuria [ 27 ].…”
Section: Pathogenesis Of Hivanmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the two risk alleles were significantly connected to higher odds of HIVAN, APOL1 genotype did not predict confidently this specific histopathology and cannot eliminate the important role of kidney biopsy in the clinical care of HIV-positive blacks who are with proteinuria more than 3.5 mg/24 h urine or unexplained kidney disease [ 38 ]. The findings of Da Silva et al in 2016 also strengthen the importance of renal biopsy in HIV patients with kidney impairment and/or proteinuria [ 27 ].…”
Section: Pathogenesis Of Hivanmentioning
confidence: 87%
“…The main renal pathological lesions of 61 HIV patients were found to be FSGS, mainly the collapsing form HIVAN in 28%, acute interstitial nephritis (AIN) in 26% and immune complex-mediated glomerulonephritis (ICGN) in 25% of the cases in Brazil. Baseline CD4 cell count ≥ 200 cells/mm 3 proved to be a protective factor against CKD (hazard ratio = 0.997; 95% confidence interval (CI): 0.994 - 0.999; P = 0.012) after 24 months follow-up [ 27 ].…”
Section: Pathological Forms Of Hivan In Africamentioning
confidence: 99%
“…The goal of antiretroviral therapy is to suppress viral load and maintain high levels of CD4 + T lymphocytes. In a cohort of 61 HIV patients treated at a hospital in southern Brazil from 2004 to 2014, who underwent renal biopsy due to renal complications (excluding those undergoing transplantation and/ or dialysis treatment) It was found that the CD4 + T cell count ≥200/mm² compared to those with CD4 + T cells <200 cells/mm² over an average period of 25 months, renal function remained more preserved, being a protective factor against the terminal renal disease or death (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The persistent suppression of viral load favored by the introduction of new drugs has provided a decrease in renal cholinergic disease and an improvement in renal function, but some anti-retroviral drugs such as tenofovir have been constantly associated with toxic effects and renal alterations (3,15,18) , as well as indinavir, cidofovir in events such as tubular damage with clinical picture of Fanconi syndrome, nephrogenic, diabetes insipidus and also renal tubular acidosis (3) .…”
Section: Discussionmentioning
confidence: 99%
“…The association between the genetic variants of the apolipoprotein 1 (APOL1) and HIVAN has been recognized since 2010, especially among the African population 22 . The classical presentation of HIVAN is defined as collapsing glomerulopathy, with nephrotic proteinuria, tubulointerstitial involvement with dilation and formation of tubular microcysts, interstitial inflammation, and tubular injury, whose manifestations may include hematuria, rapidly progressive kidney failure, and arterial hypertension 6,11,18 . In electronic microscopy, endothelial tubuloreticular inclusions (viral footprints) are highly specific and classical characteristics of HIVAN 11.18 .…”
Section: Hiv-associated Nephropathy (Hivan)mentioning
confidence: 99%